Puppets in the emotional development of childhood: Empirical reference of a case study. Initial education center "Amada Agurto de Galarza-Ecuador" (Ágora de Heterodoxias, 2021)
This research deepens the review and reflection on the conception and foundations of emotional education. Reviewing the studies, it is concluded that one of the most used educational resources to boost the emotional development of learners is the puppet. This playful instrument, combined with the teachers' daily effort, generates excellent results in the training of emotionally healthy individuals. The studies, carried out at the Centro de Educación Inicial "Amada Agurto de Galarza", diagnosed the socio-pedagogical circumstances in which its teachers guided the children and the educational resources used. It was revealed that teachers, although they have some general knowledge and occasionally apply the puppet technique, do so occasionally and do not include it as a separate element in their planning. For this reason, the general objective of the research was "to characterize the relationship that exists between the use of puppets as a teaching resource and the emotional development of children at the “Amada Agurto de Galarza Initial Education Center”. A qualitative-ethnographic approach is carried out using interviews. As a result, the project generated an integrative proposal to achieve an objective of practical application: to perform the assembly of a theatrical play based on the use of puppets, oriented towards meaningful learning and the development of positive emotions in the students of the Centro de Educación Inicial “Amada Agurto de Galarza”.
Keywords: Puppets; emotional development; emotional education; nursery education; Amada Agurto de Galarza